Whole genome sequencing of the fast-swimming Southern bluefin tuna (Thunnus maccoyii) - Zhao, Xiaomeng; Huang, Yu; Bian, Chao; You, Xinxin; Zhang, Xinhui; Chen, Jieming; Wang, Min; Hu, Cancan; Xu, Yun; Xu, Junmin; Shi, Qiong (Frontiers in Genetics, 2022)
The economically important Southern bluefin tuna (Thunnus maccoyii) is a world-famous fast-swimming fish, but its genomic information is limited. Here, we performed whole genome sequencing and assembled a draft genome for Southern bluefin tuna, aiming to generate useful genetic data for comparative functional prediction. The final genome assembly is 806.54 Mb, with scaffold and contig N50 values of 3.31 Mb and 67.38 kb, respectively. Genome completeness was evaluated to be 95.8%. The assembled genome contained 23,403 protein-coding genes and 236.1 Mb of repeat sequences (accounting for 29.27% of the entire assembly). Comparative genomics analyses of this fast-swimming tuna revealed that it had more than twice as many hemoglobin genes (18) as other relatively slow-moving fishes (such as seahorse, sunfish, and tongue sole). These hemoglobin genes are mainly localized in two big clusters (termed as “MNˮ and “LAˮ respectively), which is consistent with other reported fishes. However, Thr39 of beta-hemoglobin in the MN cluster, conserved in other fishes, was mutated as cysteine in tunas including the Southern bluefin tuna. Since hemoglobins are reported to transport oxygen efficiently for aerobic respiration, our genomic data suggest that both high copy numbers of hemoglobin genes and an adjusted function of the beta-hemoglobin may support the fast-swimming activity of tunas. In summary, we produced a primary genome assembly and predicted hemoglobin-related roles for the fast-swimming Southern bluefin tuna.